WHAT CAN COMPUTER ASSISTED LANGUAGE LEARNING CONTRIBUTE TO FOREIGN LANGUAGE PEDAGOGY? - Bangs, Paul; Cantos Gomez, Pascual (International Journal of English Studies, 2009)
The aim of this paper is twofold. On one hand, to shed new light on the uneasy relationship of Computer Assisted Language Learning (CALL) with foreign language (FL) pedagogy in the past and on the other, to explore the possible contribution of CALL to FL pedagogy. The first part of this research starts with a brief description of the first CALL experiences (behaviourist CALL) and continues with a succinct account of the present state of the art (CALL and the communicative environment). The second part of the paper points towards new and challenging directions of CALL: some assertions as to what might constitute the place of "good CALL in a language learning environment.